A Study of People Perspectives towards Water Purification Technologies using GRA Method of Multiple Attribute Decision Making in Intuitionistic Fuzzy Environment - et. al., Mary Mejrullo Merlin M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The incitement of this paper is to analyze water purifying technologies by utilizing grey relational analysis (GRA) method for multiple attribute decision making problems. The weight vectors are determined by using single-objective programming model. Water is an elixir of our life and it has several unique characteristics. Due to various unhealthy issues, drinking water still cause people sick or even destroy them, because it encompasses critical diseases-making pathogens. Water purifier will comfort and cherish the customers opposed to poisonous waterborne infections. To dumbfound this current situation GRA technique is used to solve the complication. Grey analysis is a technique which provides an agreeable explanation for existing world problems. Finally the best one is chosen by utilizing the relative relational degree.